Promoting Authentic Interaction: Investigating Student-Generated Role Play for Pragmatic Skills Development in Indonesian Vocational Efl Students - Fitri Wijayanti; Alfi Hidayatu Miqawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article examines the use of role-play in teaching pragmatic skills to the vocational students with the aim of promoting authentic interaction from Indonesian vocational students of English as a foreign language (EFL). The investigation adopts a qualitative perspective, as it recognizes the constraints of pre-set scripts in cultivating context-specific communication skills, by analyzing how student-generated role play in diverse contexts may cultivate pragmatic attunement and facilitate participation. Students in the fourth semester of an English for Tour and Travel class worked together to design workplace communication tasks based on video models and real-life experiences. Research data included classroom observations, video recordings of students’ performances, and post-project interviews. It is found that the students progressed in the use of speech acts, politeness strategies, and turn taking in spoken interactions. These roles play activities enabled not only improvised speech practice and peer feedback but also provided an opportunity for language learners to reflect cultural norms and communication intentions. The research reinforces the importance of moving away from static textbook discussions to the dynamic real-world tasks that approximate actual use of the language. It points to the need for the inclusion of pragmatic competence in speaking instruction, especially in vocational EFL contexts where work-related communication and sociopragmatic awareness are important.